27.1k views
5 votes
If f(1) = 0, what are all the roots of the function f(x)=x^3+3x^2-x-3? Use the Remainder Theorem.

User Ed Boykin
by
4.9k points

2 Answers

4 votes

I think you got it backwards! Its X=-3, X=-1, or X=1. So the answer is B. (2nd option) Well, you got it! ;)

User Marius Tibeica
by
5.7k points
4 votes
There's no if about it,


f(x)=x^3+3x^2-x-3

has a zero
f(1)=0 so
x-1 is a factor. That's the special case of the Remainder Theorem; since
f(1)=0 we'll get a remainder of zero when we divide
f(x) by
x-1.

At this point we can just divide or we can try more little numbers in the function. It doesn't take too long to discover
f(-1)=0 too, so
x+1 is a factor too by the remainder theorem. I can find the third zero as well; but let's say that's out of range for most folks.

So far we have


x^3+3x^2-x-3 = (x-1)(x+1)(x-r)

where
r is the zero we haven't guessed yet. Again we could divide
f(x) by
(x-1)(x+1)=x^2-1 but just looking at the constant term we must have


-3 = -1 (1)(-r) = r

so


x^3+3x^2-x-3 = (x-1)(x+1)(x+3)

We check
f(-3)=(-3)^3+3(-3)^2 -(-3)-3 = 0 \quad\checkmark

We usually talk about the zeros of a function and the roots of an equation; here we have a function
f(x) whose zeros are


x=1, x=-1, x=-3

User Ceezy
by
5.8k points